High Serum High Mobility Group A1 (HMGA1) Levels are associated with presence of Metabolic Syndrome: Case-control study - Mirna Faiq; Eman S. Saleh; Omar B. Fathalla (مجلة كلية الطب, 2023)
Background: Metabolic syndrome is a complex series of metabolic defects, characterized by high levels of serum glucose, hypertension, abdominal obesity, and dyslipidemia. The high mobility group AT-hook1, an architectural transcript factor, affects the homeostasis of glucose. No previous studies have been performed to examine whether HMGA1 can be secreted into the extracellular milieu.